COMPARISON OF THE EFFECTS OF THE TABARAK METHOD AND AKU CINTA ALQURAN (ACQ) METHOD ON THE ACCELERATION OF QURANIC VERSE MEMORIZATION IN EARLY CHILDHOOD AT THE RUMAH QURAN NAJMUL KHAIRAAT - Jiola, Nur Jannah (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to compare the effect of the Tabarak method and the Aku Cinta Alquran (ACQ) method on accelerating Quran memorization among early childhood students at Rumah Quran Najmul Khairaat, Boalemo. This research employed a quantitative approach with a quasi-experimental equivalent time series design. The sample consisted of 15 children aged 3–5 years who had memorized Surah Al-Fatihah. Data were collected through observation and learning outcome tests, then analyzed using descriptive and inferential statistical tests. The results showed that both Tabarak and ACQ methods positively influenced the acceleration of Quran memorization, with a significant difference in favor of the Tabarak method. These findings are expected to guide Islamic educational institutions in selecting the appropriate method to enhance early childhood Quran memorization.